Analysis of Abnormal Ground Current in 110kV Cable Line. Issue 1 (December 2020) - Xiaopo, Mao; Yi, Kan; Yaodong, Zhang; Zeqi, Huang; Xiang, Ren; Xueming, Zhou; Zhiqiang, Feng
Abstract: In recent years, with the development of economy and the rapid growth of electricity consumption, the number and length of medium and high voltage cable lines have increased rapidly. As an important part of the power transmission and distribution network, to ensure the safe and reliable operation of cable lines and reduce unplanned power outages. Based on the field test and analysis of the abnormal ground current of the 110kV Luoyong line, it is found that the cross interconnection system has many defects such as phase sequence error and identification plate indication error. It is recommended that the cable cross interconnection system carry out a segmented insulation resistance test to exclude cables. Hidden dangers such as damage to the protective layer and damage to the protective layer.